ANALYSIS OF FLOOD EXPOSURE USING DEM SRTM AND LANDSAT IMAGE IN JAKARTA - Dahlia, Siti; Nurharsono, Tricahyono; Rosyidin, Wira Fazri (Universitas Pendidikan Indonesia, 2018)
The aims of research is: 1). Making map of flood susceptibility in Special Capital Region of Jakarta area, based on geomorphology approach using DEM SRTM satellite imagery, and 2). Data inventory element at risk of flood. The method of data analysis used qualitative, based on interpretation satellite imagery data using elements of interpretation. Indicators used to result map of flood susceptibility are elevation, slope, and landform, using scoring and overlay technique. The result of research is flood susceptibility of low area is 13.613,40 ha, medium is 23.238,67 ha, and higt is 27.216,72 ha. Based on it, the majority of research area have hight of flood susceptibility. Based on spatial pattern, it showed that areas with high flood susceptibility are mostly located in the northern part of research area, and areas with the lowest flood susceptibility are majority in the southern part of researh area. The result analysis of element at risk, it showed that element at risk affected by flood for high, medium, or low level is settlement.